On the rate of growth of norming multiple and the upper and lower functions of the sum of independent random variables - Kalinauskaitė, N. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Н. Калинаускайте. О скорости роста нормирующего множителя и верхних и нижних функциях для сумм независимых случайных величин N. Kalinauskaitė. Viršutinių ir apatinių funkcijų nepriklausomų dydžių sumoms ir normuojančio daugiklio greičio klausimu